Development of a workplace intervention for sick-listed employees with stress-related mental disorders: Intervention Mapping as a useful tool - Anema Johannes R; van Oostrom Sandra H; Terluin Berend; Venema Anita; de Vet Henrica CW; van Mechelen Willem (BMC, 2007)
Abstract Background To date, mental health problems and mental workload have been increasingly related to long-term sick leave and disability. However, there is, as yet, no structured protocol available for the identification and application of an intervention for stress-related mental health problems at the workplace. This paper describes the structured development, implementation and planning for the evaluation of a return-to-work intervention for sick-listed employees with stress-related mental disorders (SMDs). The intervention is based on an existing successful return-to-work intervention for sick-listed employees with low back pain. Methods The principles of Intervention Mapping were applied to combine theory and evidence in the development, implementation and planning for the evaluation of a participatory workplace intervention, aimed at an early return-to-work for sick-listed employees with SMDs. All stakeholders were involved in focus group interviews: i.e. employees recently sick-listed with SMDs, supervisors and occupational health professionals. Results The development of the participatory workplace intervention according to the Intervention Mapping principles resulted in a structured return-to-work intervention, specifically tailored to the needs of sick-listed employees with SMDs. Return-to-work was proposed as a behavioural change, and the Attitude - Social influence - self-Efficacy model was identified as a theoretical framework. Stakeholder involvement in focus group interviews served to enhance the implementation. The cost-effectiveness of the intervention will be evaluated in a randomised controlled trial. Conclusion Intervention Mapping was found to be a promising method to develop interventions tailored to a specific target group in the field of occupational health. Trial registration ISRCTN92307123